2012
DOI: 10.1186/1472-6882-12-190
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and the 28-day repeated dose study of a Siddha medicine Nuna Kadugu in rats

Abstract: BackgroundNuna Kadugu (NK), a Siddha medicine prepared from leaves and fruits of Morinda Pubescens, used for the treatment of various skin diseases. Though NK has been widely used for several decades, no scientific report was available on its safety. Present study was undertaken to demonstrate the oral toxicity of NK in Sprague Dawley rats.MethodsAcute and 28-day repeated oral toxicity studies were performed following OECD test guidelines 423 and 407, respectively, with minor modifications. In acute oral toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In contrast, MA which is found in foods such as olives and olive oil, does not have these unwanted effects and daily consumption of olive products may provide long‐term benefit in managing arthritis. We have also demonstrated that the values obtained for MA for oral toxicity test are within the acceptable limits required by the guidelines set by Organization for Economic Co‐operation and Development (OECD) . In this study, administration of 10% MA‐containing olive powder was considered safe with (lethal dose, 50% >2000 (200 mg as MA content) mg/kg b.wt/per os (p.o.)…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, MA which is found in foods such as olives and olive oil, does not have these unwanted effects and daily consumption of olive products may provide long‐term benefit in managing arthritis. We have also demonstrated that the values obtained for MA for oral toxicity test are within the acceptable limits required by the guidelines set by Organization for Economic Co‐operation and Development (OECD) . In this study, administration of 10% MA‐containing olive powder was considered safe with (lethal dose, 50% >2000 (200 mg as MA content) mg/kg b.wt/per os (p.o.)…”
Section: Discussionsupporting
confidence: 63%
“…The histopathological studies serve as a supportive evidence for haematological and biochemical analysis (Ramaswamy et al, 2012). This study showed that the selected organs obtained from both treated animals and controls showed normal architecture, suggesting that there were no detrimental changes or morphological disturbances caused by daily oral administration of the MECN.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, it can be concluded that DC resin methanol extract is tolerated up to 2000 mg/kg body weight when administered at a single dose. In a like manner, a study performed by R Ramaswamy, N Prathyusha, R Saranya, H Sumathy, K Mohanavalli, R Priya, J Venkhatesh, C Babu, K Manickavasakam and S Thanikachalam [ 28 ] using Nuna Kadugu (a Siddha medicine prepared from leaves and fruits of Morinda Pubescens) revealed that Nuna Kadugu can be classified under category-5 when administered at single dose 2000 mg/kg in accordance with Globally Harmonised System of Classification and Labelling of Chemicals, and this provides a direct relevance for protecting human and animal health.…”
Section: Discussionmentioning
confidence: 99%
“…The SD rats were randomly divided into six groups of 10 rats each ( n = 10/group, 5 males and 5 females) as mentioned elsewhere [ 28 ]. Four groups were administered daily with DC resin methanol extract at different concentration dissolved in 10% DMSO and two groups administered with the vehicle by using oral gavage.…”
Section: Methodsmentioning
confidence: 99%